Synthesis of 5-nitrovanillin in low temperature as cyanide anion sensor - R Rahmawati; Syarifa Wahidah Al Idrus; Supriadi Supriadi; Lalu Sulman (The University of Mataram, 2021)
In terms of organic sensor, the molecular structure affects a compound's ability to be used as a colorimetric chemosensor. Here, we present a simple synthesis technique for 5-nitrovanillin sensor. It has been successfully synthesized using nitric acid as a source of nitro groups. Dichloromethane DCM was used as a solvent, and the synthesis was carried out at low temperatures (under 5Â°C). The method produces a good yield. The nitro group attached to the chemosensor plays a role in prolonging the electron delocalization. Its effect is in the process of anion recognition by the chemosensor. The formation of a sensor-analyte complex between the chemosensor and anion produces a color change in the solution